"To observe well … and thence to make himself rules": John Locke's principles and practice of child healthcare. Issue 1 (1st June 2007) - Williams, A N
Abstract : It is often forgotten that the philosopher John Locke (1632–1704) was a highly regarded physician with a lifelong interest in medicine and was frequently consulted on medical matters, including the health of children. This child health aspect in Locke's history has been largely ignored, with even modern commentaries on Locke and medicine giving it only a cursory mention. However, it is clear that, in child health, Locke's influence is far more substantial than GF Still's and George Jackson's opinions, which limited Locke solely to Thoughts concerning education (1692/3). That a fundamental reappraisal of Locke's role in child healthcare is necessary and that his place as a pioneer of modern child healthcare needs to be proclaimed are emphasised here. As modern day child healthcare has evolved to embrace advocacy and learning disability, Locke's importance through his influence on paediatrics, child healthcare and human rights becomes more evident. Locke's influence in child healthcare comes not only through his other celebrated philosophical writings, but also through extensive personal correspondence and case records. As well as throwing light onto the 17th century aspects of child healthcare, Locke, through his enquiry and self-evident humility in his correspondence on medical matters, inspires and educates us with his pragmatic approach to the practice of medicine.